The effect of reading literary fiction on the theory of mind skills among persons with schizophrenia and normal controls - Fekete, Judit; Pótó, Zsuzsanna; Varga, Eszter; Hebling, Dóra; Herold, Márton; Albert, Noémi; Pethő, Borbála; Tényi, Tamás; Herold, Róbert (Frontiers in Psychiatry, 2023)
Introduction Recent research data suggest that theory of mind (ToM) skills may improve after reading literary fiction. However, beside this short term favorable effect, regular long-term reading of literary fiction may also support ToM development or may improve ToM performance. The presence of impaired ToM abilities is well-documented in schizophrenia; however, the role of reading in these deficits is unknown. In the present study our aim was to assess the effect of prior reading experiences on theory of mind performance in patients with schizophrenia, and in healthy controls. Materials and methods ToM assessment was done with the Short Story Task, which is based on the interpretation of a Hemingway short story. After reading the short story, questions were asked in an interview format regarding comprehension, explicit and implicit ToM skills, then comparative analysis of schizophrenia patients was performed (n = 47) and matched to a normal control (n = 48) group concerning deficits of ToM abilities. Participants were also stratified according to their prior reading experiences. Results Previous reading experience was associated with better comprehension and explicit ToM performance both in patients with schizophrenia, and in healthy controls. However, the explicit ToM performance of patients with prior reading was still weaker compared to healthy controls with reading experiences. Path model analysis revealed that reading had a direct positive effect on ToM, and an indirect effect through improving comprehension. Conclusions Prior reading experience is associated with better ToM performance not just in healthy controls but also in patients living with schizophrenia. Previous reading experience also improves comprehension, which in turn has a favorable impact on ToM. Our results support the idea that literary fiction reading may have a therapeutic potential in the rehabilitation of schizophrenia.